Path of code - SACILOTE, Gianluca; AZEVEDO, Guilherme; SANTOS, Gustavo Ferreira Rocha; NUNES, Pedro Henrique Martins (023, 2025)
O Path of Code é um jogo 2D criado para ajudar quem está começando a aprender programação de um jeito leve, divertido e acessível. Desenvolvido na engine Godot, ele ensina conceitos básicos como variáveis, condicionais, loops e funções através de desafios interativos que colocam o jogador em contato direto com a lógica de programação sem depender de métodos tradicionais e teóricos demais. A proposta do jogo é tornar o aprendizado mais envolvente, especialmente para quem nunca teve contato com esse universo. Além disso, o projeto foi pensado para rodar em computadores simples, o que permite que mais pessoas possam jogar e aprender, mesmo sem equipamentos potentes. Com isso, o Path of Code vai além do ensino técnico, ele busca tornar o primeiro contato com a programação algo acolhedor, acessível e inspirador para todos.

Path of Code is a 2D game created to help those who are just starting to learn programming in a light, fun and accessible way. Developed in the Godot engine, it teaches basic concepts such as variables, conditionals, loops and functions through interactive challenges that put the player in direct contact with programming logic without relying on traditional and overly theoretical methods. The game's proposal is to make learning more engaging, especially for those who have never had contact with this universe. In addition, the project was designed to run on simple computers, which allows more people to play and learn, even without powerful equipment. Another important point is the care for the well-being of players: the game can be played in pairs, which encourages teamwork, socialization and can even help relieve stress and anxiety. With this, Path of Code goes beyond technical education — it seeks to make the first contact with programming something welcoming, accessible and inspiring for everyone.
Keywords: Jogos de computador; Informação e Comunicação